Efeito da estimulação não invasiva do nervo vago na modulação autonômica cardíaca dos pacientes com COVID-19: estudo clínico, controlado, cego e randomizado - Souza, Paulo Henrique Leite (2022)
Objective: To evaluate the effects of transcutaneous auricular vagus nerve stimulation (taVNS) on cardiac autonomic modulation in individuals affected by COVID-19. Design: Clinical trial, randomized, blinded, placebo-controlled. Location: It was held at Professor Lydia Storopoli Hospital. Participants: Individuals affected with COVID-19, situated within the first ten days of infection, a random sample of 84 participants diagnosed with COVID-19 was approached to participate in the study, of which 45 completed the survey. 39 participants were excluded. Intervention: taVNS was applied twice a day for seven consecutive days, with 90 minutes of stimulation for each session. An electrode was applied on the left tragus and on the left clavicle for the experimental group, the control group followed the same protocol as the experimental group, but the equipment remained turned off. Outcome measure: Heart rate variability (HRV) was assessed before and after seven days of treatment. Results: There were no changes in HRV results. In LF the pre results were CI 95% (40.5 to 62.9) and post CI 95% (48.4 to 70.1) for the a-taVNS group, and for the s-taVNS group they were pre CI 95 % (37.7 to 61.6) and post 95% CI (45.7 to 69.9). There was also no significance between the 95% CI groups (-14.4 to 18.4) with p= (0.812). In HF the pre results were CI 95% (36.9 to 59.2) and post CI 95% (29.1 to 41.4) for the a-taVNS group, and for the s-taVNS group they were pre CI 95 % (38.0 to 61.9) and post CI 95% (30.1 to 54.0). There was also no significance between the 95% CI groups (-18.1 to 14.5) with p= (0.829). In the LF/HF ratio, the pre results were 95% CI (0.56 to 5.18) and post 95% CI (3.15 to 7.76) for the a-taVNS group, and for the s-taVNS group were pre 95% CI (0.33 to 5.26) and post 95% CI (0.83 to 5.76). There was also no significance between the 95% CI groups (-1.21 to 5.54) with p= (0.208). Conclusion: taVNS showed no effects on HRV modulation in individuals affected with COVID-19.